Effects of treated wastewater on selected soil nutrients and biological properties - Kganyago, Zaphania Mmadichaba (My University, 2019)
Water scarcity poses significant risks to global food security. The use of treated wastewater for irrigation could be a sustainable remedy for water scarcity in arid to semi-arid regions. Furthermore, it has been the most readily available source of water which can serve as an adaptation strategy to shortage of irrigation water. The objectives of the study were to determine (1) whether different disposal points following wastewater treatment could have effects on the quality of treated wastewater used for irrigation at the University of Limpopo (UL) experimental farm and (2) the response of selected critical nutrients, microbial and enzyme activities on soils irrigated with treated wastewater at the UL Experimental Farm. Water samples were collected monthly at three disposal points, namely, the exit point of treated wastewater from the treatment plant (Pond 16), the entry point into the night-dam and the exit point from the night-dam at the UL Experimental Farm. The water samples were analysed for pH, electrical conductivity (EC), sodium (Na), nitrate (NO3-), phosphate (PO42-), sulphate (SO42-), salinity, magnesium (Mg), calcium (Ca), potassium (K), chlorine (Cl), total dissolved solids (TDS), total soluble salts (TSS), lead (Pb), copper (Cu), cadmium (Cd), zinc (Zn), Ascaris lumbricoides, Escherichia coli, Shigella spp., Salmonella spp. and Vibrio cholera. A field experiment was conducted on a separate 4-ha virgin field (VF), cultivated field (CF) and fallowed field (FF), with soil samples collected from 0- 5, 5-15 and 15-30 cm soil depth in each field and analysed for pH, EC, mineralisable P, NH4+, NO3-, organic carbon (OC), active carbon (AC), potential mineralized nitrogen (PMN), fluorescein diacetate (FDA) and phosphatase (PTS) enzyme activity. All data were subjected to ANOVA using Statistix 10.1. The treated wastewater had, at the three sampling points, significantly different EC, Na, NO3-, PO42-, SO42-, Cu, Zn, Shigella spp., V. cholerae, A. lumbricoides and E. coli, whereas salinity, pH, Mg, Ca, K, Cl and Cd were not affected by the sampling point. Generally, the night-dam entry and exit points had significant increases in PO42-, K and Ca when compared to Pond 16 exit. In contrast, the flow of wastewater from Pond 16 through the furrow to the entry and exit of the night-dam resulted in decreases of Na, NO3- and Cl. The exit point of water from the night-dam at UL Experimental Farm had the least harmful materials, rendering it the safest point with the best water quality for irrigation. In the field study, NH4+, NO3- and PMN were significantly different in soil depth. However, NO3- field × depth interaction effects were not significantly different. In contrast to all soil parameters, FDA and PTS activity for both soil depth and field × depth interaction effects were highly significantly different. The EC and pH were not affected by soil depth or field type. The negative effects of treated wastewater were mainly observed in the cultivated field. In conclusion, treated wastewater with fallowing could be used as the best approach to overcome water shortages, with the uses having the potential to reduce the need to apply high synthetic chemical fertilisers. Keywords: water reuse, disposal points, essential nutrients, microbial activities
Thesis (M. Sc. (Soil Science)) -- University of Limpopo, 2019
Keywords: Water reuse; Disposal points; Essential nutrients; Microbial activities; Water reuse - Law and legislation; Aerated package treatment systems